Rifaximin improves survival in cirrhotic patients with refractory ascites: A real-world study - Lv, Xin-Yue (World J Gastroenterol, 2020)
BACKGROUND: Rifaximin has been shown to reduce the incidence of hepatic encephalopathy and other complications in patients with cirrhosis. However, few studies have investigated the effect of rifaximin in cirrhotic patients with refractory ascites. AIM: To evaluate the effects of rifaximin in the treatment of refractory ascites and to preliminarily explore its possible mechanism. METHODS: A total of 75 cirrhotic patients with refractory ascites were enrolled in the study (50 in a rifaximin and 25 in a control group). Patients in the rifaximin group were divided into two subgroups according to the presence of spontaneous bacterial peritonitis and treatment with or without other antibiotics (19 patients treated with rifaximin and 31 patients treated with rifaximin plus intravenous antibiotics). All patients received conventional treatment for refractory ascites, while patients in the rifaximin group received oral rifaximin-α 200 mg four times daily for at least 2 wk. The ascites grade, fasting weight, liver and kidney function, and inflammatory factors in the plasma were evaluated before and after treatment. In addition, the gut microbiota was determined by metagenomics sequencing to analyse the changes in the characteristics of the gut microbiota before and after rifaximin treatment. The patients were followed for 6 mo. RESULTS: Compared with the control group, the fasting weight of patients significantly decreased and the ascites significantly subsided after treatment with rifaximin (P = 0.011 and 0.009, respectively). The 6-mo survival rate of patients in the rifaximin group was significantly higher than that in the control group (P = 0.048). The concentration of interferon-inducible protein 10 decreased significantly in the rifaximin group compared with that in the control group (P = 0.024). The abundance of Roseburia, Haemophilus, and Prevotella was significantly reduced after rifaximin treatment, while the abundance of Lachnospiraceae_noname, Subdoligranulum, and Dorea decreased and the abundance of Coprobacillus increased after treatment with rifaximin plus intravenous antibiotics. The gene expression of virulence factors was significantly reduced after treatment in both subgroups treated with rifaximin or rifaximin plus intravenous antibiotics. CONCLUSION: Rifaximin mitigates ascites and improves survival of cirrhotic patients with refractory ascites. A possible mechanism is that rifaximin regulates the structure and function of intestinal bacteria, thus improving the systemic inflammatory state.